2009
DOI: 10.1166/jnn.2009.440
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Growth of Vertically-Oriented High Aspect Ratio Titania Nanotubes by Rabid Anodization in Fluoride-Free Media

Abstract: Vertically-oriented high aspect ratio titania nanotube bundles have been grown by a potentiostatic anodization of titanium sheet in fluoride-free electrolytes. The anodization conditions like the applied voltage were optimized for the synthesis of titania nanotubes in HClO4 and NaCl electrolyte. The resulting nanotubes have a length of about 30 microm, outer diameter about 40 nm, inner pore size of about 10 nm and the aspect ratio was 750:1 by anodization in 0.1 M perchloric acid of pH approximaately 1 at appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…12 In summary, TiO 2 nanotubes could be obtained not only in the fluoride or chloride-containing electrolytes, but also in the halidefree electrolytes. 22 The interesting results demonstrate that the J e generation and oxygen bubbles are necessary to form nanopores or nanotubes, because the J e becomes the predominant mode of charge transport under the breakdown condition. 24 Anion incorporation and generation mechanism of electronic current.-Electronic current and oxygen evolution during anodizing process are admitted in many literatures.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…12 In summary, TiO 2 nanotubes could be obtained not only in the fluoride or chloride-containing electrolytes, but also in the halidefree electrolytes. 22 The interesting results demonstrate that the J e generation and oxygen bubbles are necessary to form nanopores or nanotubes, because the J e becomes the predominant mode of charge transport under the breakdown condition. 24 Anion incorporation and generation mechanism of electronic current.-Electronic current and oxygen evolution during anodizing process are admitted in many literatures.…”
Section: Resultsmentioning
confidence: 95%
“…When the applied voltage is high and anodic oxide is localized breakdown, porous anodic oxide can be obtained. Fahim et al 22 have demonstrated that TiO 2 NTs could be obtained during Ti anodization in H 2 SO 4 solutions. The current-time curve during Ti anodization in H 2 SO 4 is quite similar to that obtained in fluoride-containing electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…Self-organized oxide tube arrays can be fabricated by electrochemical anodization of a suitable metal foil under specific anodic conditions and proper electrolytes [18][19][20][21][22][23]. For instance, highly ordered TiO 2 nanotube arrays are typically grown by electrochemical anodization of titanium foils [23].…”
Section: Introductionmentioning
confidence: 99%
“…The titanium dioxide white layer leaves the substrate and breaks down gradually in one dimension developing vertically oriented nanotubes in the electrolyte in the powder form as indicated by eqn (1)-(4). 15,16,38 Ti + 2H 2 O / TiO 2 + 4H + + 4e À…”
Section: Rapid Breakdown Anodizationmentioning
confidence: 99%